2013
DOI: 10.1055/s-0033-1336630
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against a beneficial effect of irisin in humans

Abstract: Brown adipose tissue has gained interest as a potential target to treat obesity and metabolic diseases. Irisin is a newly identified hormone secreted from skeletal muscle enhancing browning of white fat cells, which improves systemic metabolism by increasing energy expenditure in mice. The discovery of irisin raised expectations of its therapeutic potential to treat metabolic diseases. However, the effect of irisin in humans is unclear. Analyses of genomic DNA, mRNA and expressed sequence tags revealed that FN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(138 citation statements)
references
References 40 publications
8
126
0
4
Order By: Relevance
“…Our results also go against works that put in doubt the FNDC5/irisin beneficial effects (26). Thus, the present study corroborate clinically with early studies in animals and in vitro (1,2) that associated FNDC5/irisin stimulus with a metabolic improvement in humans.…”
Section: Discussionsupporting
confidence: 91%
“…Our results also go against works that put in doubt the FNDC5/irisin beneficial effects (26). Thus, the present study corroborate clinically with early studies in animals and in vitro (1,2) that associated FNDC5/irisin stimulus with a metabolic improvement in humans.…”
Section: Discussionsupporting
confidence: 91%
“…Our group has recently published an analysis of genomic DNA, mRNA and expressed sequence tags indicating that FNDC5, the gene encoding the precursor of irisin, is present in rodents and most primates [100]. However, in humans we observed a mutation that changes the conserved start codon ATG to ATA.…”
Section: Key Facts: Myokines As Therapeutic Targetsmentioning
confidence: 79%
“…As summarised in Table 1, in vitro studies have shown that IL-6 increases myotube fatty acid oxidation and lipolysis via AMPK activation [32,33]. [46] No data available regarding endocrine metabolic effects of muscle-derived BDNF IL-6 ↑ GLUT4 translocation [19,20] ↑ Glucose uptake [15,19] ↑ Glycogen synthesis [18,20] ↑ Fatty acid oxidation [18][19][20] ↑ Lipolysis [32][33][34] Liver: ↑ Glucose production [23] Intestine: ↑ GLP-1 secretion of L cells [52] Pancreas: ↑ Beta cell proliferation [52] ↑ GLP-1 secretion of alpha cells [52] ↑ Proliferation and ↓ apoptosis of alpha cells [51] IL-13 ↑ Glucose uptake [28] ↑ Glucose oxidation [28] ↑ Glycogen synthesis [28] Liver: ↓ Glucose production [29] IL-15 ↑ Fatty acid oxidation [43] Adipose tissue: ↓ Lipid accumulation [44,45] ↑ Adiponectin secretion [44] Irisin No data available Adipose tissue: ↑ White to brown shift [98,111] No effect on browning [100] FGF21 ↑ Glucose uptake [99,136] Adipose tissue: ↑ White to brown shift [99] ↑ Glucose uptake [99] ↑ Adiponectin secretion [127,128] Liver: ↑ Fatty acid oxidation [137] ↑ Gluconeogenesis [137] Recently, a study using isolated mouse muscle reported that IL-6...…”
Section: Myokines and Metabolic Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The hormone was isolated in mice but the same group also detected circulating levels of this hormone in humans. A great debate is ongoing, after some previous findings questioned the relevance of the hormone (91,92). Raschke suggested that humans are unable to cleave FDNC5 and the detected irisin may just be laboratory interferences and even exogenous irisin administration in human cells does not appear to have the expected result.…”
Section: What Is the Real Prevalence Of Brown Adipose Tissue? Conceptmentioning
confidence: 99%